Roasting-leaching experiments on glauconitic rocks of Bakchar ironstone deposit (Western Siberia) for evaluation their fertilizer potential; Applied Clay Science; Vol. 162 - Rudmin M. A. Maksim Andreevich; Oskina Yu. A. Yuliya Aleksandrovna; Banerjee S. Santanu; Mazurov A. K. Aleksey Karpovich; Soktoev B. R. Bulat Rinchinovich; Shaldybin M. V. Mikhail Viktorovich (2018, 2018)
Title screen